The European Elections 2019 in Greek – Cypriot print Media. The Positions of the Newspapers Alithia and Haravgi in May 2019 - Antoniades, Euripides (My University, 2020)
The role of the media during the European election is extremely important as it is the dominant form factor of news and public communication. In this context, both civil society and political actors are the two additional players in the triangle of shaping and influencing communication for social issues. The purpose of this paper is to investigate the agenda and the way in which the news of Greek Cypriot print media was framed. Specifically, this research examines the main topics identified in the printed media during the pre-election period of the European elections in Cyprus in May 2019. Also, this research focuses on how the issues of the news appeared. This research seeks to answer the above questions, thus enriching the research gap found in the existing literature. From a theoretical point of view, this article adopts the theories of the Agenda Setting and Framing, because as interrelated theories they can explain the research theme. In addition, for the purposes of the survey, a mixed methodological approach was applied, with the research adopting quantitative content analysis and framing. Our methodology was based on elements of content quality analysis and aims to analyse the content of the text message, discourse and form and involves five stages: 1. The procedure of compiling the empirical evidence. 2. The isolation of items (units recorded). 3. The classification of units into categories. 4. The quantity conversion and measurement of items (codification). 5. Analysis and interpretation of data. The findings showed that the Media Agenda during the pre-election period included a wide range of topics. The topics that had the highest frequency appearance in the media were the economy, society, and environment issues.
Keywords: Cyprus; European elections 2019; Print media; Agenda setting; Framing; News